Mandarin Language Material using Artificial Intelligence for Z-Generation Student - Sunarti Sunarti; Ting Hie Ling; Chong Pei Qi; Amira Eza Febrian Putri (Journal of Development Research, 2022)
This aims of research to develop an artificial intelligence-based Mandarin learning media for the millennial generation that is interesting and can be learned anywhere. The content of the latest material determined in this study is a descriptive text of the coronavirus in Indonesia. This study uses the Research and Development ADDIE design. The research data was obtained from the results of questionnaires, and validation of material and media experts. In the initial observation, it was found that 96.1% of students aged 15 – 20 years in Malang City are familiar with the use of technology in everyday life, therefore it is necessary to develop a technology-based interactive learning media that can support teachers in teaching students who are also Generation Z. After testing the material, it was found that this learning media has very good quality that score is 84. This research is also considered capable of making prototypes that have very good quality in terms of media that the total final score is 85.